The Use Of Sabu Language By Second Generation Of Savunese Migrants Living In Kupang - Zizilia Monalisa Djami Riwu; Sebastianus Fernandes; Gracia M.N. Otta (Journal of Humanities, Social Sciences, and Education, 2025)
This thesis is entitled : “The Use of Sabu Language by Second Generation of Savunese Migrants living in Kupang”. The research problems of this study are; (1) How is the acquisition process of Sabu language undergone by the second generation Savunese migrants living in Kupang? (2) In what domains is Sabu language used by the second generation of Savunese migrants living in Kupang?. The study aims are; to find out how is the acquisition process of Sabu language undergone by the second generation Savunese migrants living in Kupang and to find out in what domains is Sabu language used by the second generation of Savunese migrants living in Kupang. This study used qualitative descriptive method. The subject of this research was the second generation of Savunese migrants living in Kupang. There were 10 informants. The instruments of data collection are; list of questions, writing tools such as books and pen/pencil, audio-recording devices and cameras and a list of words or sentences to be translated by the informant as an additional or supporting instrument. The result shows that there are 8 informants also acquire the Sabu language from their parents and family neighbors, but 2 informants acquire the Sabu language only from their parents or family. There are two domains where the second generation uses the Sabu language; the private domain and the social domain.